The Role of Good Corporate Governance and Whistleblowing System Mechanisms on Fraud Disclosure: Empirical Study on Banking Sub-Sector Companies Listed on The Indonesia Stock Exchange In 2015-2020 - Rossaliani, Sindy; Subiyanto, Bambang; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the effect of the Role of Good Corporate Governance Mechanism measured through the Independent Audit Committee and Managerial Ownership, as well as the Whistleblowing System on Fraud Disclosure in Banking Sub-Sector Companies listed on the Indonesia Stock Exchange in 2015-2020. The source of this research data uses quantitative secondary data, research data comes from the annual report of banking industry companies listed on the Indonesia Stock Exchange in 2015-2020. In sampling for this study used a purposive sampling method. The data analysis techniques used are multiple linear regression and hypothesis testing using t-statistical tests that have been processed on SPSS 25 to test regression coefficients. Based on the results of partial research, it was found that the Independent Audit Committee had a negative and significant effect on banking fraud disclosure, managerial ownership had a positive and significant effect on banking fraud disclosure, while the Whistleblowing System did not have a significant effect on banking fraud disclosure.